STRATEGI DALAM MENINGKATKAN DAYA SAING MADRASAH ALIYAH NEGERI 2 KOTA PADANG - Jefry Nofriansyah; Herri; Syafrizal (Halu Oleo University, 2025)
This study aims to analyze strategy formulation in improving the competitiveness of Madrasah Aliyah Negeri (MAN) 2 Kota Padang. The research method used is descriptive qualitative with data collection techniques through interviews, documentation, and literature studies. Data analysis was carried out using SWOT analysis, IFE-EFE matrix, and Grand Strategy Matrix. The results show that MAN 2 Kota Padang has several internal strengths such as the integration of national and religious curricula, flagship programs, and community loyalty. However, there are still weaknesses in terms of limited infrastructure and intense competition with other leading schools in Padang. Strategies that can be implemented include strengthening differentiation through religion- and technology-based flagship programs, improving human resource quality, and enhancing branding and networking. In conclusion, strategy formulation based on SWOT and Porter provides a more structured policy direction in enhancing madrasah competitiveness.